A review on cloud computing adoption from the perspectives of providers and clients - Suhaimi, Mohd Adam; Hussin, Husnayati; Md Ali, Asma; Mohamad Puad, Noor Hazwani (IEEE, 2019)
Cloud computing received a lot of interests from various organizations since the technology was introduced. The potential of cloud computing as a new IT acquisition approach that provide strategic value to businesses has been discussed broadly including looking at issues and challenges in cloud computing adoption. However, there is a dearth of prior studies to discover the issues and challenges in cloud computing adoption from the providers’ perspective as most of past researches mainly focus on the clients’ perspective. In this paper, issues and challenges of cloud computing adoption from both client’s and provider’s perspectives are discussed, based on reviewing past literature related to cloud computing adoption in various countries. The result of the review indicate that there are differences in the issues which become the main concerns of clients and providers of cloud computing services. This paper contributes towards understanding cloud computing adoption from multi-perspectives and help researchers to set future agenda.